The SmartNTx-study: a prospective, randomized controlled trial to investigate additional interventional telemedical management versus standard aftercare in kidney transplant recipients - Schiffer, Mario; Pape, Lars; Wolff, Julia K.; Gertges, Raoul; Visconti, Vanessa; Reichert, Karen; Pfau, Anja; Dieterle, Anne; Sauerstein, Katja; Kribben, Andreas; Boss, Kristina; Karaterzi, Sinem; et al. (Frontiers in Nephrology, 2025)
BackgroundRegular follow-up care after kidney transplantation is performed in transplant centers together with local nephrologist practices in Germany. Patients after kidney transplantation have to fulfill many tasks and manage their disease, follow a complex therapeutic regimen, communicate with the transplant center and home nephrologists, and coordinate doctor appointments. It has been shown that mHealth solutions such as mobile phone applications (apps) can support patients in their self-management. However, stand-alone apps have limitations and ideally, the mHealth solutions are embedded in a holistic treatment approach, including healthcare professionals.MethodsWe will conduct a 1-year, prospective, randomized, 2-armed, parallel group multicenter trial in three German Kidney Transplant Centers (KTCs) to demonstrate that additional and continuous interventional telemedical management will improve health after kidney transplantation in patients of all ages. Therefore, a composite endpoint of seven key outcome variables [fewer hospitalizations, shorter length of hospitalization, less development of de novo donor-specific antibody (DSA), better medication adherence, lower tacrolimus intra-patient variability, better blood pressure control, and better renal function after kidney transplantation]was defined. All the patients will receive the same routine post-transplant aftercare. The patients in the interventional arm will receive additional predefined telemedical management, including regular telemedicine visits and automatic bidirectional data transfer (e.g., vital signs, wellbeing, medication plan, and laboratory data together with a chat option) between the patient at home and the KTC through a certified smartphone app. If necessary, a home nephrologist can be included in the automatic data transfer. In the interventional arm, the iBox score will be used to better detect patients at risk for early graft failure and drug-drug interactions will be regularly checked with certified software.DiscussionThe study aims to prolong patient and graft survival through additional telemedical services in order to reduce avoidable hospitalizations, improve treatment of co-morbidities, and improve adherence through patient empowerment, which should result in lower health care costs, and better quality of life of patients after kidney transplantation.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT05897047.